Design of Digital Learning for Preventing Human Error in Ship Accidents - Shanty Yahya (International Journal of Marine Engineering Innovation and Research, 2024)
Shipping safety is a main priority in all industries, including the shipping industry. The shipping industry must provide guarantee of the safety of people and cargoes in the shipping process. Ensuring shipping safety will support increased world trade. The development of the shipping industry has increased due to world trade, but this increase is not consistent with shipping safety standards. Shipping safety is low due to the quantity of ship accidents that have caused fatality and property loss. Humans error are one of the factors causing ship accidents. Inadequate skill and competence of ship crew is one of the indicators in human error that can cause ship accidents. Inadequate skill and competence of ship crew due to limited time and space to learn and improve their skills and competency. Purpose of this study is to develop maritime learning application prototype, that can be used crews to learn by ship and improve their competence and skills with flexible time and place. The name is application is Smart Shipping. The method used in this research is the waterfall method. The result of this research is an e-learning Prototype that was designed based on user’s competence and subject expertise as well as the position on the ship. Material in this e-learning can be downloaded for offline learning. Furthermore, e-learning provides learning evaluation to measure user understanding through questions, exercises, and tests. The shipping industry can use this e-learning as a preventive action of ship accidents due to human error.